TAX PLANNING AND TAX RESEARCH IN THE TAX ACCOUNTING COURSES. - Dickerson, W. E. (The Accounting Review, 1957)
Abstract The accountant most certainly needs some knowledge of tax planning regardless of the area of his specialization. Most business executives are aware that there are opportunities to save on taxes. The nature of these opportunities is not nearly so well known. Consequently, they are frequently overlooked and unnecessary tax obligations are incurred. It is important that tax saving opportunities be recognized when they arise. While it is sometimes possible to take advantage of opportunities which were overlooked on an earlier date, the usual result of tardy recognition is a lost opportunity. Taxes cannot be neglected because it is net income after taxes that is important. In view of the importance of tax planning in the management of business, it seems desirable that instruction in the subject be made available to all students of business administration. The interests and needs of different classes of students vary widely and must be considered in determining the extent and timing of their work in tax planning. Organization of a separate course in tax planning has a number of disadvantages.